Visible-light-assisted multimechanism design for one-step engineering tough hydrogels in seconds - Cong Wang (Nature Portfolio, 2020)
Tough hydrogels capable of efficient mechanical energy dissipation are difficult to be patterned and/or printed which limits their application. Here the authors show a one-step, biocompatible and general strategy to prepare tough soft hydrogels with high-resolution 2D/3D microstructures quickly under mild conditions.